The value construction of visual style in electronic advertising discourse A semiological analytical reading of the advertising flash of the mobile phone operator Djezzy via the YouTube website - نبيل شايب (International Journal of Social Communication, 2023)
The importance of the research problem is reflected in the fact that the electronic form as the subject of communication and the electronic form as the semantic form need to apply the semiotic analysis method to infer the semantic implication of electronic information as a new achievement, Semantic investment is allowed to approach semantics purposefully in the semantic field In the semantic field, multiple data are fused together in some way to form a symbolic dimension; By relying on the close complementarily of Roland Barthes and Roman Jacobson, we find that the value model is recognized and interpreted when considering its reference context, which makes the semiotic study of electronic advertising language legitimate. According to syntactic and semantic rules by reading the flashing symbols of mobile operator Djezzy, we find that sometimes the formatted value structure semantics . This is mainly because the social lighting of the target recipient Algerian consumers or the so-called recipients is not representative, which leads to the dysfunction in the process of electronic publicity communication.